Condensation frosting and freezing of impact water droplets on cold surfaces - Zhu, Fangqi (Nanyang Technological University, 2022)
The accretion of ice/frost stemming from condensation frosting and freezing of impact water droplets is pervasive in both nature and industry, causing enormous losses every year worldwide especially in aviation and transportation. Most existing studies regarding condensation frosting focus on the anti-frosting potential by leveraging the ice-liquid or ice-vapor interactions on two-dimensional structured surfaces. Little is known about condensation frosting on one-dimensional surfaces with temperature gradient. This thesis first reports on the non-uniform condensate morphologies on a cantilevered microfiber during condensation due to the competition between conductive thermal resistance within the fiber and condensation heat transfer resistance on the fiber surface. Scaling analyses were provided to reveal the underlying physics. During the frosting phase, the nucleation of supercooled liquid microdroplet is triggered at locations where ice bridges are upon contact instead droplet-substrate interfaces. Furthermore, an inter-droplet ice wicking regime is reported where the liquid droplet is sucked by physical contact of ice bridge, different from the classical inter-droplet ice bridging. Such phenomenon results from the competition between wicking dynamics and nucleation crystallization timescales. Intriguingly, the frosting morphology on the microfiber demonstrates a similar trend to the condensate morphology. Moreover, the directional migration and easy assembling of melted water can be achieved by tailoring the fiber length and cooling temperature during defrosting, and well explained by the analytical models proposed. Additionally, a unique distribution pattern of condensed droplets is found during condensation on stainless-steel mesh, with one droplet atop every other knot. Such phenomenon arises from the extent of the region of inhibited condensation imposed by the central knot within the smallest periodic unit of the distribution pattern. Lattice Boltzmann simulation is implemented to obtain the water vapor concentration, and the pattern region under various ambient temperature and mesh specifications is predicted based on a proposed model validated with experimental data. The dynamics of water droplets impacting on isothermal surfaces (with the same temperature as water) have been extensively studied over the years, and so have the freezing dynamics of sessile droplets on cold substrates. However, the underlying mechanisms of freezing of impact water droplets on cold surfaces remain elusive. This thesis then focuses on the impact behavior of water droplets on cold surfaces. A triple condensate halo is found during a water droplet impacting at low velocity upon a cold surface. Due to the interaction of droplet impact and vapor mass diffusion during droplet spreading and cooling, two condensation stages occur, engendering this unique condensate halo with three distinctive bands. Furthermore, five different freezing morphologies of impact droplets were discovered when room-temperature water droplets impacted perpendicularly on a sufficiently cooled superhydrophilic surface, depending upon the impact velocity and substrate temperature. The formation of such morphologies results from the competition between the timescales associated with droplet solidification heat transfer and impact hydrodynamics. A phase diagram is developed based on scaling analyses to demonstrate how the freezing morphologies are governed by droplet impact and solidification related timescales which well interprets the experimental findings. For inclined surfaces, another four different freezing morphologies are found which can be partially explained by modifying the scaling analyses applied in the perpendicular impact. Quite different from the cases on hydrophilic surfaces, the frozen impacted droplets can self-peel completely and become easily removable from a hydrophobic surface sufficiently cooled. The intriguing phenomena are rationalized by comparing the strength of thermal contraction of ice, ice-ice cohesion, and ice-substrate adhesion. In addition, a model is developed to characterize the peeling and bending of the frozen impacted water droplet, which can qualitatively explain the experimental observations.